Occupational exposure assessment in professionals who manipulate and administer antineoplastic drugs in a university hospital in Southern Brazil. (July 2021) - Ness, Sandro Luis R; Mascarenhas, Marcello Á; Arbo, Marcelo D; Tonietto, Bruna D; Cestonaro, Larissa V; dos Santos, Nícolas G; Garcia, Solange Cristina; Ferreira, Charles F; Capp, Edison
Introduction: Our goal was to demonstrate the effects of occupational exposure to antineoplastic drugs on oxidative stress parameters and DNA damage in health professionals who manipulate and administer antineoplastic drugs in a University Hospital in Southern Brazil. Methods: The case-control study with a longitudinal design, involved 64 individuals, 29 of them pharmacists, pharmacy technicians and nurses who were occupationally exposed to antineoplastic drugs and 35 professionals who were not exposed. Gene mutations were determined by micronucleus from salivary fluid; DNA damage by comet assay and oxidative stress parameters in whole blood were also evaluated. Results: All workers exposed to antineoplastic drugs used personal protective equipment (PPE). It was demonstrated that the total nonprotein thiol and thiobarbituric acid reactive substances levels showed interaction between group and time, with higher levels one week after handling/administration of antineoplastic drugs in the exposed group (GEE, p ≤ 0.0001 and p = 0, 013, respectively). Additionally, there was a group effect on the activities of the catalase and glutathione peroxidase antioxidant enzymes (GEE, p = 0.027 and p ≤ 0.0001, respectively), and workers occupationally exposed to antineoplastic drugs had higher enzyme activities compared to those not exposed. No genotoxic damage was demonstrated through the evaluated parameters. Conclusions: Despite the correct use of PPE, professionals occupationally exposed to antineoplastic drugs were more susceptible to oxidative stress than those not exposed. The evaluation of the studied parameters is especially important for the definition of conducts and practices in the area, always in search of guaranteeing the establishment of a rational policy to protect workers' health.